PENYAWAHAN TERUS MENERUS MEMACU PERECEPATAN PELAPUKANAN TANAH - Robertus Sudaryanto (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2009)
Title : Rice-field Cultivation Continuously was Accelerated Soil Weathering. This research was aimed to find out the existence of soil acceleration development indication as the result of the cultivation which was done continuously and for a long period. This research was done by analyzing soil samples which were taken from non-rice-field soil and cultivated soil which had been used for 20 years, 30 years, and 40 years in cultivation intensity once a year, twice a year and three times a year. Those analyzed soils had the same primary substances. The sand and clay content in the soil was chosen as the indicator of the soil weathering acceleration because of rice-field cultivation. From the data gathered, it was analyzed the connection with the cultivation length and cultivation pattern through the similarities of correlation and regression. The research result showed that: soil which was used continuously and for a long period would tend to decrease the sand content but increase the clay content in the soil. The increase of clay and the decrease of sand in the soil indicated the high soil weathering intensity which would fasten the soil development. Therefore, it is suggested that it is not needed to do puddling phase while land preparation phase, because puddling tend to mineral weathering, and if it is possible cultivation by no tillage soil system could be done. Keywords: sand and clay content in the soil, rice-field cultivation, and soil development